Effects of cigarette smoking on plasma concentration of the appetite-regulating peptide ghrelin - Koopmann, Anne; Bez, Jennifer; Leménager, Tagrid; Hermann, Derik; Dinter, Christina; Reinhard, Iris; Hoffmann, Heiko; Wiedemann, Klaus; Winterer, Georg; Kiefer, Falk (Annals of nutrition & metabolism, 2015)
Background: Weight gain is a common but only a partially understood consequence of smoking cessation. Existing data suggest modulating effects of the orexigenic peptide ghrelin on food intake. The aim of the present study was to investigate the effect of tobacco withdrawal on plasma concentration of acetylated and total ghrelin. Methods: Fifty four normal-weighted smokers and 30 non-smoking healthy controls were enrolled in our study. Concentrations of acetylated and total ghrelin were measured in blood plasma drawn two hours after a standardized meal and three hours after the smokers smoked their last cigarette. The severity of tobacco addiction was assessed based on cotinine plasma concentration, the Fagerström Test for Nicotine Dependence (FTND) and the number of cigarettes smoked per day. Results: The plasma concentration of acetylated ghrelin, but not total ghrelin, was significantly higher in smokers than in non-smokers. Moreover, we found significant negative correlations between acetylated ghrelin and all measures of the severity of nicotine dependence. Conclusions: Early abstinence from tobacco smoking seems to be associated with increased plasma concentration of the orexigenic peptide acetylated ghrelin. This could be one reason for increased food craving during nicotine withdrawal and subsequent weight gain. Smokers might compensate these effects by increasing tobacco intake.
Gesehen am 26.11.2018